2021
DOI: 10.3390/jpm11111212
|View full text |Cite
|
Sign up to set email alerts
|

Ace2 and Tmprss2 Expressions Are Regulated by Dhx32 and Influence the Gastrointestinal Symptoms Caused by SARS-CoV-2

Abstract: Studies showed that the gastrointestinal (GI) tract is one of the most important pathways for SARS-CoV-2 infection and coronavirus disease 2019 (COVID-19). As SARS-CoV-2 cellular entry depends on the ACE2 receptor and TMPRSS2 priming of the spike protein, it is important to understand the molecular mechanisms through which these two proteins and their cognate transcripts interact and influence the pathogenesis of COVID-19. In this study, we quantified the expression, associations, genetic modulators, and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…ACE2 was evenly distributed and active from the terminal ileum to the DC. These data are in accordance with data from other studies reporting that ACE2 is expressed throughout the small and large intestine, 9,[33][34][35][36][37] although some studies have reported that ACE2 expression is higher in the ileum than in the colon. [34][35][36][37] Intestinal ACE2 actively removes C-terminal single neutral amino acid from nutrient peptides, which are then uptaken by the neutral amino acid transporter B 0 AT1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ACE2 was evenly distributed and active from the terminal ileum to the DC. These data are in accordance with data from other studies reporting that ACE2 is expressed throughout the small and large intestine, 9,[33][34][35][36][37] although some studies have reported that ACE2 expression is higher in the ileum than in the colon. [34][35][36][37] Intestinal ACE2 actively removes C-terminal single neutral amino acid from nutrient peptides, which are then uptaken by the neutral amino acid transporter B 0 AT1.…”
Section: Discussionsupporting
confidence: 92%
“…These data are in accordance with data from other studies reporting that ACE2 is expressed throughout the small and large intestine, 9,[33][34][35][36][37] although some studies have reported that ACE2 expression is higher in the ileum than in the colon. [34][35][36][37] Intestinal ACE2 actively removes C-terminal single neutral amino acid from nutrient peptides, which are then uptaken by the neutral amino acid transporter B 0 AT1. 38,39 Interestingly, it has been reported that ACE2 expression is required for the expression, proper trafficking, and functioning of B 0 AT1, 39 which is abundantly expressed in the ileum.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the implications of ACE2 upregulation would lead to specific studies based on different symptoms in old and young patients. Patients with ACE2 overexpression in the gastrointestinal tract are associated with more diarrhea ( 59 ). In fact, there is evidence demonstrating a direct association between endothelitis and severe COVID-19 ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…To identify the regulators of SHMT1 in RCC, we performed an analysis by genome‐wide association studies (GWAS). As a high‐energy resource of GWAS, the BXD family is widely used in the study of medicine and disease mechanism, including the search for the regulatory network of genes in diseases 30,31 . Figure 4A shows the gene expression levels of Shmt1 in kidney tissue from 53 BXD mouse strains and their corresponding parental strains.…”
Section: Resultsmentioning
confidence: 99%